Markers predicting progression of human immunodeficiency virus-related disease. - Tsoukas, C M (1994)
Human immunodeficiency virus (HIV) interacts with the immune system throughout the course of infection. For most of the disease process, HIV activates the immune system, and the degree of activation can be assessed by measuring serum levels of molecules such as beta 2-microglobulin and neopterin, as well as other serum and cell surface phenotype markers. The levels of some of these markers correlate with clinical progression of HIV disease, and these markers may be useful as surrogate markers for development of clinical AIDS. Because the likelihood and timing of development of clinical AIDS following seroconversion, for any particular individual, are not readily predictable, the use of nonclinical disease markers has become critically important to patient management. Surrogate markers of HIV infection are, by definition, measurable traits that correlate with disease progression. An ideal marker should identify patients at highest risk of disease progression, provide information on how long an individual has been infected, help in staging HIV disease, predict development of opportunistic infections associated with AIDS, monitor the therapeutic efficacy of immunomodulating or antiviral treatments, and the easily quantifiable, reliable, clinically available, and affordable. This review examines the current state of knowledge and the role of surrogate markers in the natural history and treatment of HIV infection. The clinical usefulness of each marker is assessed with respect to the criteria outlined for the ideal surrogate marker for HIV disease progression.